2019
DOI: 10.3390/membranes9070085
|View full text |Cite
|
Sign up to set email alerts
|

Characterization of the Fouling Layer on the Membrane Surface in a Membrane Bioreactor: Evolution of the Foulants’ Composition and Aggregation Ability

Abstract: In this study, the characteristics of membrane foulants were analyzed with regard to morphology, composition, and aggregation ability during the three stages of transmembrane pressure (TMP) development (fast–slow–fast rise in TMP) in a steady operational membrane bioreactor (MBR). The results obtained show that the fouling layer at the slow TMP-increase stage possessed a higher average roughness (71.27 nm) and increased fractal dimension (2.33), which resulted in a low membrane fouling rate (0.87 kPa/d). A hig… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 8 publications
(3 citation statements)
references
References 30 publications
(39 reference statements)
0
3
0
Order By: Relevance
“…Moreover, it was demonstrated that large numbers of PSB cells were immobilized into porous macrospheres, which could be beneficial to enhancing the performance of the MBR in treating wastewater. It was noted that the filtration capacity of the membrane was closely related to the characteristics of sludge flocs in the bioreactor [ 44 , 45 ]. Therefore, in order to understand what influences immobilized photosynthetic bacteria in terms of membrane fouling, the various characteristics of the immobilized microorganism were investigated in detail.…”
Section: Resultsmentioning
confidence: 99%
“…Moreover, it was demonstrated that large numbers of PSB cells were immobilized into porous macrospheres, which could be beneficial to enhancing the performance of the MBR in treating wastewater. It was noted that the filtration capacity of the membrane was closely related to the characteristics of sludge flocs in the bioreactor [ 44 , 45 ]. Therefore, in order to understand what influences immobilized photosynthetic bacteria in terms of membrane fouling, the various characteristics of the immobilized microorganism were investigated in detail.…”
Section: Resultsmentioning
confidence: 99%
“…5c). It was found that these disordered nanostructures on the dragonfly wing were more effective in reducing protein adhesion than the ordered cicada replicated surface, thus the dragonfly wing surface was highly effective in inhibiting the adhesion of bacteria (i.e., Gram-negative and -positive) due to the disruption of cell surface in contact with the nanostructures [80][81][82][83]. Figure 5d shows the four stages of E. coli death process, respectively.…”
Section: Dragonfly Wingsmentioning
confidence: 99%
“…However, membrane fouling, especially biofouling, has been the main obstacle for the wide application of MBRs [3]. It is widely known that biofouling starts with the deposition of foulants during the initial stages of membrane filtration, resulting in the development of additional fouling layers on the membrane surface [4]. The initial fouling layer affects the intrinsic properties of the membrane and thereby the subsequent development of additional layers [5].…”
Section: Introductionmentioning
confidence: 99%